INOVASI RITUAL DALAM PRAKTIK KEAGAMAAN MASYARAKAT PESANTREN: INTEGRASI INVENTED TRADITION, KONSTRUKSI SOSIAL, DAN EPISTEMOLOGI BAYANI, BURHANI, IRFANI DALAM DIALEKTIKA TUDUHAN BID'AH - Fadlillah; Ach. Maimun; Moh Diyaul Murtadho; Abdullah; Suji; Moh. Chalilurrosyid; Moh. Kurdi (Jurnal Ikhtibar Nusantara, 2026)
This article examines ritual innovation within pesantren communities as a form of religious creativity rooted in the continuity of Islamic scholarly traditions in the Indonesian archipelago. The study departs from the tension between the social and da'wah needs of pesantren communities to adapt religious rituals to socio-cultural change, and the accusations of bid'ah emerging from puritan Islamic groups. Unlike previous studies that tend to discuss pesantren rituals either descriptively-historically or theologically-normatively in isolation, this study offers a novelty in the form of an integrative analytical model that combines three theoretical frameworks at once: Eric Hobsbawm's invented tradition, Peter L. Berger's social construction of reality, and Mohammed Abed al-Jabiri's bayani-burhani-irfani epistemology, to provide a more comprehensive reading of the dialectic between traditional creativity and bid'ah accusations. This research employs a qualitative descriptive method with sociological-philosophical approaches and a library research technique. The findings reveal that ritual innovation in pesantren is not merely a deviation from Islamic orthodoxy, but an adaptive mechanism that bridges religious texts and local cultural realities, while also reflecting an epistemological clash between literalist bayani reasoning and the fusion of bayani, burhani, and irfani that is alive within pesantren tradition. Therefore, the discourse of bid'ah should not be viewed solely as a rigid theological conflict, but as a dialectical contestation over religious authority, interpretation, and cultural legitimacy in contemporary Indonesian Islam.